BALANCE DETERMINATION BETWEEN PARAMETERS OF ROAD TRANSPORT - , Л. С., С. В. (Municipal economy of cities. Series: «Economy science», 2018)
The article discusses topical issues of developing models for the transport stream behavior in conditions of increased density and uncertainty in measuring their parameters. The substantiation of a modeling method choice and a kind of dependence of stream parameters according to their practical application for rational functioning of a city transport network is resulted. A sequence of the basic parameters calculation of the fundamental diagram is proposed to determine the range of change in the flow intensity, the maintenance of which in the transport movement control can prevent the occurrence of tarmac situations on the roads. The article presents the results of experimental research on the Kharkov transport network. Keywords: transport simulation, fundamental diagram, intensity, capacity, balance of parameters.